Pemberdayaan Peran Kelompok Usaha Muda Melalui Inovasi Produk Lokal Mie Ganyong - Muhammad Syah Fibrika Ramadhan; Asmi Ayuning Hidayah; Meyfita Esti; Devilia Aziz (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Mie ganyong is a local product that uses canna flour as the basic ingredient. Through the Youth Awareness and Pioneering Development program (PKKP) from the Central Java Youth, Sports and Tourism Office, mie ganyong are transformed into a contemporary food favored by spicy lovers, namely Seblak Minyong. The purpose of this service is to improve the village economy through local product innovation in Majasari Village, Bukateja District, Purbalingga Regency. The method used is lecture and practice/demonstration. The raw materials used for this processing are mie gelang, seblak crackers, spiral macaroni, chain crackers, and cuankie tongue. In its implementation it went well and received full support from village youth, local village officials, as well as the Purbalingga Youth, Sports and Tourism Office.